+0  
 
+3
62
3
avatar+294 

Find the constant coefficient when the polynomial \(3(x - 4) + 2(x^2 - x + 7) - 5(x - 1)\) is simplified.

 Feb 27, 2021
 #1
avatar+771 
0

The constant coefficient is the number with x^0. 

So, we just need to find those. 

3(x-4) has the -12. (3*-4)

2(x^2-x+7) has a 14. (2*7)

-5(x-1) has a 5. (-5*-1)

Now, we just sum everything together. :))

-12+14+5 = 7

I hope this helped. 

 

=^._.^=

 Feb 27, 2021
 #2
avatar+294 
+3

Thank you!

calvinbun  Feb 27, 2021
 #3
avatar+771 
0

You're welcome. :))

 

=^._.^=

catmg  Feb 27, 2021

22 Online Users

avatar
avatar
avatar